2022
DOI: 10.4251/wjgo.v14.i9.1798
|View full text |Cite
|
Sign up to set email alerts
|

To scope or not - the challenges of managing patients with positive fecal occult blood test after recent colonoscopy

Abstract: BACKGROUND Colorectal cancer (CRC) is a major health problem. There is minimal consensus of the appropriate approach to manage patients with positive immunochemical fecal occult blood test (iFOBT), following a recent colonoscopy. AIM To determine the prevalence of advanced neoplasia in patients with a positive iFOBT after a recent colonoscopy, and clinical and endoscopic predictors for advanced neoplasia. METHODS The study recruited iFOBT pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Previous reports suggest that TCS should be repeated when there is concern about the quality of the previous TCS or in high‐risk patients, such as older age or family history of CRC. 17 In our study, the results of a previous TCS affected those of a TCS after a positive FIT result, and patients with previous AN, ≥3 adenomatous lesions, and size ≥10 mm showed higher ADR and AN detection rates in TCS after FIT. Reportedly, the results of a previous TCS can affect the results of surveillance TCS.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Previous reports suggest that TCS should be repeated when there is concern about the quality of the previous TCS or in high‐risk patients, such as older age or family history of CRC. 17 In our study, the results of a previous TCS affected those of a TCS after a positive FIT result, and patients with previous AN, ≥3 adenomatous lesions, and size ≥10 mm showed higher ADR and AN detection rates in TCS after FIT. Reportedly, the results of a previous TCS can affect the results of surveillance TCS.…”
Section: Discussionmentioning
confidence: 50%
“…Several studies have reported the association between repeat colonoscopy for patients with positive FIT results and recent colonoscopy. 16 , 17 , 18 , 19 , 20 Kim et al. reported the results of TCS for patients aged ≥50 years with positive FIT results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation